Religious Participation and Economic Conservatism. Issue 4 (27th March 2013) - Gaskins, Ben; Golder, Matt; Siegel, David A.
<x xml:space="preserve">Abstract</x> Why do some individuals engage in more religious activity than others? And how does this religious activity influence their economic attitudes? We present a formal model in which individuals derive utility from both secular and religious sources. Our model, which incorporates both demand‐side and supply‐side explanations of religion, is unusual in that it endogenizes both an individual's religious participation and her preferences over economic policy. Using data on over 70 countries from the pooled World Values Survey, we find that religious participation declines with societal development, an individual's ability to produce secular goods, and state regulations on religion, but that it increases with inequality. We also find that religious participation increases economic conservatism among the poor but decreases it among the rich. Our analysis has important insights for the debate about secularization theory and challenges conventional wisdom regarding the relationship between religious participation and economic conservatism.